EFFECTIVENESS OF TREATMENT OF PATIENTS WITH DRUG-RESISTANT FORMS OF PULMONARY TUBERCULOSIS IN THE REPUBLIC OF TAJIKISTAN - P.U. MAKHMUDOVA; R.U. MAKHMUDOVA; K.A. ZAKIROVA; P.U. MAKHMUDOVA; R.U. MAKHMUDOVA; K.A. ZAKIROVA (Avicenna Tajik State Medical University, 2018)
Objective: To conduct a comparative analysis of the effectiveness of treatment of drug-resistant (DR) forms of tuberculosis (TB) in the Republic of Tajikistan, including combination infection of DR TB/HIV for 2014-2017 years by region of the country. Methods: The analysis of official statistic data on DR forms of TB with combined HIV infection from 2014 to 2017 was carried out in the framework of the implementation of the "National Strategic Plan for Population Protection from Tuberculosis in the Republic of Tajikistan for 2015-2020 years". Results: Number of new cases of DR forms of TB with the started treatment in 2014 was 46.3%. In 2017, this number increased to 56%, which confirms the growth of TB with DR among new cases in the country. The number of cases with DR TB among the re-infected during this period decreased from 58% to 37%. The results of the treatment effectiveness of the DR TB cohort of 2015 at the level of the republic among cured and completed treatment were 58%. The failure of treatment - 7.8%, separation from treatment - 14.4%, lethality - 17.7%, continue treatment - 2.1%. The highest rate of treatment effectiveness of DR TB is observed in Dushanbe (72.8%). This is due to the fact that in all institutions organized DOTS cabinets, are available all diagnostics methods, have almost complete security personnel; more quality control of treatment is conducted. The failure to treat patients with DR forms of tuberculosis is 9.1%, separation from treatment is 4.5%, and mortality is 13.6%. Conclusion: The comparatively high rate of treatment effectiveness of patients with DR TB in Dushanbe city (72.8%) proves the positive impact of such factors as the availability of modern diagnostic equipment and system are provided by qualified personnel treatment.